Analytical Forms of the Verb as a Structural Feature of the Grammar of the Chuvash Language - Eduard E. Lebedev (Publishing house "Sreda", 2021)
The study is devoted to the consideration of the analytical forms of the verb in the Chuvash language and the issue of their inclusion in the system of grammatical categories along with synthetic forms. The work was carried out on the material of samples of Chuvash fiction using the functional-semantic method. The article presents a brief history of the study of this issue both in general in Turkic studies and in Chuvash linguistics. The author emphasizes that the existing undefined status of such combinations in the grammars of the Chuvash and other Turkic languages does not contribute to an adequate description of the corresponding forms and categories. Due to the fact that one of the components of analytical forms completely or partially loses its nominative meaning, while acquiring an official grammatical meaning, they have not become the subject of detailed study in the syntax section. But in morphology, they are also not studied to the proper extent due to the fact that more than one word is formally present in such combinations. The author believes that when applying the functional-semantic approach to the study of such combinations, it becomes clear that functionally these forms do not differ from synthetic forms and should be the subject of description at the morphological level. The conclusions of the research are supported by examples of specific analytical forms and are as follows: these forms are an integral part and structural feature of the Chuvash language grammar. As a prospect for further research, we can name a detailed study of the functional and semantic component of the analytical forms of the verb and the development of their classification.